DEVELOPMENT OF INTERNET OF THINGS (IOT) TECHNOLOGY AND ITS APPLICATION ON ROOM COOLING SYSTEM - DWI PRASETYO (NIM : 10214059), JOSHUA
Internet of Things is a cyber physical system, a system which can conclude some information from big data and use them for feedback so that system can adapt well to the change in its environment. Internet of Things has many applications in this modern world, one of them is in energy management. In this research, Internet of Things is applied on room cooling system. The room cooling system works with fuzzy logic control so that it can adjust the time for on-off state of the system. Temperature data obtained by the system is processed to obtain physical quantities, which are thermal characteristics, which can be used to determine when the system goes on/off. In this research, variations of control, which are variation of configuration type, variation of how long the system goes on/off in triangle configuration, and variation of width of the triangle configuration have been conducted. ItÃ‚Â’s concluded that configuration which has the most triangle function has the most optimal temperature range and average temperature; longer on time can decrease minimal temperature, but mapping and inference rule that are not optimized will cause a larger temperature range; the most optimal triangle configuration is the configuration which is not too wide and too narrow, that is the configuration with membership function interval is 1 up to 3. RC value obtained when the compressor is turned off are the thermal characteristics of room and the values are similar. RC value obtained when the compressor is turned on are usually larger than RC value obtained when the compressor is turned off and does not depend on the temperature difference between outdoor and indoor.